Formulation Development and Characterization of Transdermal Gel Containing Fenoprofen- Loaded Solid Lipid Nanoparticle - Verma, Navneet Kumar; Naidu, M.A.; Kumar Gaur, Praveen (Journal of Neonatal Surgery, 2025)
The topical administration of anti-inflammatory drugs by Solid Lipid Nanoparticles (SLNs) has enormous potential. This study aimed to develop a topical Fenoprofen-loaded SLNs gel to improve the efficacy of the well-known antifungal drug in the treatment of wound healing. Materials and Methods: In order to create Fenoprofen SLNs, concentrations of surfactants were chosen as independent factors, and particle size and %Entrapment Efficiency were chosen as dependent variables. The produced Fenoprofen -SLNs were examined using zeta potential, polydispersity index, and particle size measurements. Additionally, Carbopol 934 was used to incorporate the improved Fenoprofen-SLN formula into gel. The outcomes demonstrated that Fenoprofen -SLNs had colloidal sizes. Fenoprofen -SLNs were discovered to have a particle size and an Entrapment Efficiency. The in vitro release, among other assessment criteria, was evaluated for the improved SLN gels. The study's conclusions imply that the topical gels made with Fenoprofen -loaded SLNs must be effective in the management of wound healing..